CTA Strategy Refresh 2018-2020 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
In 2016 CTA launched a new Strategic Plan for 2016–2020 to address the major challenges small-scale producers in the ACP face. The aim of the plan was to contribute to the development of inclusive, profitable and sustainable value chains and markets that are nutrition sensitive, climate-smart and benefit small-scale producers, women and youth. The strategy has successfully provided direction for the organisation as it builds a programme to deliver an ambitious set of targets. This Strategy Refresh, which builds on the 2016–2020 plan, follows extensive discussions with partners, staff and the Executive Board and takes into account new challenges and opportunities that CTA must respond to in order to stay on track and meet its targets.